Behaviour of a three-dimensional uniaxial magnet near the critical point in an external field - Kozlovskii, M.P.; Pylyuk, I.V.; Prytula, O.O. (Condensed Matter Physics, 2004)
The behaviour of a three-dimensional magnet with a one-component order parameter near the critical point in a homogeneous external field is investigated. The calculations are performed in the case when the field and temperature are dependent and related by some expression (the system tends to the critical point along some trajectory). The high- and low-temperature regions in the vicinity of Tc ( Tc is the phase transition temperature in the absence of an external field) are considered. It is shown that in the weak fields the system behaviour is described in general by the temperature variable, but in the case of the strong fields the role of the temperature variable is not dominant. The corresponding expressions for the free energy, susceptibility and other characteristics of the system are obtained for each of these regions. Досліджена поведінка тривимірного магнетика з однокомпонентним параметром порядку поблизу критичної точки у випадку наявності однорідного зовнішнього поля. Розрахунки виконані у випадку, коли величини поля та температури є залежними та зв’язаними між собою певним співвідношенням (система прямує до критичної точки по певній траєкторії). Розглянуті області температур вищих та нижчих за Tc ( Tc – температура фазового переходу при відсутності поля). Показано, що при слабких значеннях поля поведінка системи описується в основному температурною змінною, а для випадку сильних полів роль температурної змінної не є домінуючою. Для кожної з цих областей отримані відповідні вирази для вільної енергії, сприйнятливості та інших характеристик системи в околі критичної точки.